Recognised tools for public registration of eGovernment stakeholders - Rodríguez Ayuso, Juan Francisco (Universidad Nacional del Litoral, 2021)
The main objective of this research study is to offer a systematic analysis of consent in the processing of personal data of minors under the General Data Protection Regulation and the Organic Law on the Protection of Personal Data and the Guarantee of Digital Rights. Specifically, besides studying consent in depth as a fundamental legal basis, we dissect the essential contours of the e-signature as the most suitable instrument for guaranteeing the provision of this consent, focusing on the special features that this presents when those who intervene as controllers are the Public Administrations.